Privileged multi-target directed propargyl-tacrines combining cholinesterase and monoamine oxidase inhibition activities. (31st December 2022) - Chrienova, Zofia; Nepovimova, Eugenie; Andrys, Rudolf; Dolezal, Rafael; Janockova, Jana; Muckova, Lubica; Fabova, Lenka; Soukup, Ondrej; Oleksak, Patrik; Valis, Martin; Korabecny, Jan; Marco-Contelles, José; et al.
Abstract: Twenty-four novel compounds bearing tetrahydroacridine and N -propargyl moieties have been designed, synthesised, and evaluated in vitro for their anti-cholinesterase and anti-monoamine oxidase activities. Propargyltacrine 23 (IC50 = 21 nM) was the most potent acetylcholinesterase (AChE) inhibitor, compound 20 (IC50 = 78 nM) showed the best inhibitory human butyrylcholinesterase ( h BChE) profile, and ligand 21 afforded equipotent and significant values on both ChEs (human AChE [ h AChE]: IC50 = 0.095 ± 0.001 µM; h BChE: IC50 = 0.093 ± 0.003 µM). Regarding MAO inhibition, compounds 7, 15, and 25 demonstrated the highest inhibitory potential towards h MAO-B (IC50 = 163, 40, and 170 nM, respectively). In all, compounds 7, 15, 20, 21, 23, and 25 exhibiting the most balanced pharmacological profile, were submitted to permeability and cell viability tests. As a result, 7-phenoxy- N -(prop-2-yn-1-yl)-1, 2, 3, 4-tetrahydroacridin-9-amine hydrochloride (15 ) has been identified as a permeable agent that shows a balanced pharmacological profile [IC50 ( h AChE) = 1.472 ± 0.024 µM; IC50 ( h BChE) = 0.659 ± 0.077 µM; IC50 ( h MAO-B) = 40.39 ± 5.98 nM], and consequently, as a new hit-ligand that deserves further investigation, in particular in vivo analyses, as the preliminary cell viability test results reported here suggest that this is a relatively safe therapeutic agent. Graphical Abstract: UF0001